Determinação de resíduos de agrotóxicos em leite em pó empregando dispersão da matriz em fase sólida, GC-MS/MS e UHPLC-MS/MS - Izeppi, Lenise Janaina Pertile (2019)
The milk powder is a food of complex composition (protein, fat, carbohydrate, vitamins, etc.). It plays a fundamental role in child nutrition due to nutritional factors related to cognitive ability. In recent years, the indiscriminate use of pesticides has been evidenced by the results of pesticide residue determination in foods. Thus, this research aimed to develop and validate a vortex-assisted matrix solid phase dispersion analytical method for determination of pesticide residues in bovine milk powder by GC- MS/MS and UHPLC-MS/MS. In the development of the method it was proposed an experimental design with different conditions of sample mass (0.5, 1 and 1.5 g), sorbent mass (1, 2 and 3 g) and solvent volume (5, 6 and 7 mL). In addition, different sorbents such as (C18, Florisil ®, PSA, alumina, diatomaceous earth and chitosan) were tested. The homogenization was performed with the aid of ceramic homogenizers and vortex. In the validation results the linear range of the method was 0.36 to 14.4 µg L-1 to UHPLC-MS/MS for 66 pesticide residues and 0.7 to 28.8 µg L-1 to GC-MS/MS for 45 pesticide residues. The accuracy and precision obtained by VA-MSPD for all pesticides were adequate with recoveries between 70 and 120% and RSD ≤ 20%. The evaluated compounds showed LOQ between 10, 25 and 50 µg kg-1 and LOD between 3, 7.5 and 15.0 µg kg-1.